2020
DOI: 10.1002/ana.25948
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status Mediates Racial Differences Seen Using theAT(N)Framework

Abstract: Objectives African Americans are at greater risk for developing Alzheimer's disease (AD) dementia than non‐Hispanic whites. In addition to biological considerations (eg, genetic influences and comorbid disorders), social and environmental factors may increase the risk of AD dementia. This paper (1) assesses neuroimaging biomarkers of amyloid (A), tau (T), and neurodegeneration (N) for potential racial differences and (2) considers mediating effects of socioeconomic status (SES) and measures of small vessel and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 51 publications
0
58
0
Order By: Relevance
“…In another study, even after accounting for genetic markers (APOE ε4 and ABCA7) and Aβ42, African Americans were found to have lower CSF p-tau, t-tau, and Aβ40 [ 140 ]. No differences between races were observed in the results of PiB PET [ 153 , 155 ] or Tau PET [ 155 ]. In patients with MCI, African Americans have been found to have significantly lower levels of total Tau in CSF than non-Hispanic Whites [ 156 ].…”
Section: Biomarkers and Ethnicity In Alzheimer’s Diseasementioning
confidence: 99%
“…In another study, even after accounting for genetic markers (APOE ε4 and ABCA7) and Aβ42, African Americans were found to have lower CSF p-tau, t-tau, and Aβ40 [ 140 ]. No differences between races were observed in the results of PiB PET [ 153 , 155 ] or Tau PET [ 155 ]. In patients with MCI, African Americans have been found to have significantly lower levels of total Tau in CSF than non-Hispanic Whites [ 156 ].…”
Section: Biomarkers and Ethnicity In Alzheimer’s Diseasementioning
confidence: 99%
“…67 For example, a cross-sectional imaging study, using a mediation analysis, found that the Area Deprivation Index accounted for almost all the higher risk of AD found in African American participants. 69…”
Section: Racial Discriminationmentioning
confidence: 99%
“…This provides valuable insights into the biological differences in disease profiles among a multi-ethic cohort and adds to the literature demonstrating the importance of understanding the biological mechanisms of MCI and dementia across racial and ethnic groups. Recent work has demonstrated that SES factors were significantly associated with MRI-based markers of neurodegeneration among African Americans [29]. In the HABLE study, SES factors (i.e., acculturation, household income) were significantly related to MRI-based neurodegeneration among Mexican Americans, but not for non-Hispanic whites.…”
Section: Discussionmentioning
confidence: 86%